Constructing Figure-Eight Structures by Inner-Bond Cleavage - Fukui, Norihito (Synlett, 2025)
Contemporary synthetic strategies in organic chemistry rely heavily on the stepwise formation of bonds between constituent fragments of the target compound, namely the bottom-up approach. However, this dependency poses significant challenges for the preparation of several classes of complex molecules, such as figure-eight molecules, despite their desirable functionality in advanced materials. Recently, we have developed an oxidative inner-bond-cleavage approach that enables a scalable, catalytic, and enantioselective synthesis of figure-eight aromatic macrocycles. This Synpacts article summarizes the background, results, and outlook of our achievement.1 Introduction2 Background3 Our Contribution4 Conclusion and Outlook
Keywords: nonplanar π-systems; figure-eight molecules; inner-bond cleavage; asymmetric synthesis; circularly polarized luminescence